Stable Isotope Dynamics (δ13C and δ15N) in Neritic and Oceanic Waters of the North Atlantic Inferred From GPS-Tracked Cory’s Shearwaters - Ceia, Filipe R.; Cherel, Yves; Paiva, Vitor H.; Ramos, Jaime A. (Frontiers in Marine Science, 2018)
Intrinsic markers, such as stable isotopes, are a powerful approach to trace wildlife movements because they do not require initial marking of the organism. The main limitation of the isotopic method is the lack of knowledge in spatio-temporal patterns and dynamics of stable isotopes in marine environments, especially at local scales. Here, we combine GPS-tracks and isotopic signatures from Cory’s shearwaters as a model species to define isoscapes in the North Atlantic, and assess δ13C and δ15N dynamics, from local to regional spatial scales. Tracking data and blood samples were collected seasonally (during pre-laying and chick-rearing periods) across 6 years (2010–2015) from a total of 191 birds breeding at both neritic and oceanic environments. Tracked birds encompassed a large latitudinal and longitudinal area of the mid-North Atlantic, from the Eastern to Central North Atlantic. Overall, the δ13C and δ15N values of birds’ plasma over the region ranged from -20.2 to -16.2‰, and from 10.8 to 15.5‰, respectively. As expected, strong biogeographic isotopic patterns were found in δ13C values at a regional scale, mostly driven by an inshore/offshore gradient and chlorophyll a concentration. Although a moderate expression of spatial isotopic gradients on δ15N values (i.e., latitudinal and inshore/offshore) in the whole region, these were primarily influenced by temporal drivers (i.e., annual variability). At a local scale (i.e., in a radius of 100 km around the colony, within the neritic environment), both δ13C and δ15N values were very influenced by temporal drivers, suggesting that wide-ranging top consumers are hard to trace locally. This study shows that the δ13C values of marine top consumers are good indicators of the foraging habitat at a regional scale in the mid-North Atlantic, especially in terms of inshore/offshore gradients and areas of higher productivity.